Drug release nanoparticle reinforced hydrogel as well as preparation method and application thereof
The porous hydrogel formed by crosslinking drug nanoparticles wrapped by phospholipid-acrylate polymers with acrylated biodegradable polymers in diabetic wound dressings has solved the problem of insufficient adaptability of traditional dressings in diabetic wound environments, achieving a significant improvement in sustainable drug release and wound healing.
Patent Information
- Application Number
- CN202411794060.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional wound dressings are not adaptable enough in diabetic wound environments, cannot continuously release active substances, and are difficult to accelerate wound healing, which can easily damage the wound.
A drug-release nanoparticle reinforced hydrogel is developed to encapsulate active pharmaceutical ingredients through phospholipid-acrylate polymers and crosslink with acrylated biodegradable polymers to form a porous hydrogel to achieve stable loading and long-lasting release of the drug.
The sustainable release of drugs is achieved, significantly improves wound healing and skin regeneration rates, reduces scar formation, and provides good biocompatibility and mechanical properties.
Smart Images

Figure CN119792184A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical technology, and in particular to a drug-releasing nanoparticle-enhanced hydrogel and a preparation method and application thereof. Background Art
[0002] Diabetic wounds pose significant challenges due to impaired angiogenesis and dysregulated inflammation, leading to chronic wounds. However, it remains challenging for conventional wound dressings to meet the complex healing process. Currently, standard clinical wound dressings (e.g., gauze, films) are not adequately adapted to the diabetic wound environment because they neither continuously release active substances nor accelerate the wound healing process, and often encounter the risk of adhesion and damage to diabetic wounds. Hydrogels contain a large amount of water, providing a moist environment for patients and can be used as wound dressings. Hydrogels have structural similarities to soft tissues and can be added with therapeutic ingredients that promote diabetic wound healing. Composite hydrogels have been shown to have enhanced functionality when mixed directly with particle suspensions by different methods. However, these hydrogel therapeutic platforms have limitations, including uncontrolled release, complex pre-treatment reaction conditions, and changes in the hydrophilicity of the hydrogel.
[0003] Drug-loaded biomaterials have emerged as a promising platform for diabetic wound healing. Aspirin, as one of the most potent nonsteroidal anti-inflammatory drugs (NSAIDs), inhibits the cyclooxygenase-2 (COX-2) enzyme. COX-2 is a known mediator of prostaglandin E2 (PGE2) secretion and is involved in promoting inflammatory conditions. It has been demonstrated that alleviation of the early inflammatory phase by COX-2 inhibition affects diabetic eye disease. In addition, the use of local anesthetics (LA) for diabetic foot ulcers significantly reduces wound pain in patients during and after dressing changes and promotes wound healing by inhibiting tumor necrosis factor α (TNF-α). Addressing acidosis in inflamed tissues reduces the anesthetic efficacy of the administered LA drug. A transdermal absorbable adhesive patch has been developed that contains a basic anti-inflammatory analgesic and a local anesthetic as an absorption enhancer. However, an effective drug delivery method to achieve multidrug compatibility and long-term therapeutic effects is still lacking. Therefore, the development of composite materials with comprehensive functionalities to accelerate wound healing is essential to improve the quality of life of diabetic patients. Summary of the invention
[0004] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention aims to provide a drug-releasing nanoparticle-enhanced hydrogel and a preparation method and application thereof.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a drug-releasing hydrogel, comprising:
[0007] Drug nanoparticles, including active pharmaceutical ingredients encapsulated by phospholipid-acrylate polymers;
[0008] A porous hydrogel comprising an acrylated biodegradable polymer and a porogen cross-linked to form a porous hydrogel;
[0009] The porous hydrogel is loaded with the drug nanoparticles.
[0010] In the present invention, the phospholipid-acrylate polymer has good biocompatibility, encapsulates the active drug ingredient to form spherical nanoparticles (DNP) of regular shape, and provides uniform assembly and outer layer distribution of acrylate for the drug nanoparticles, thereby increasing their zeta potential value, thereby improving the stability of their distribution in water; on the other hand, the introduction of a porogen into the acrylated biodegradable polymer can introduce pores into the hydrogel, thereby improving the accessibility of the drug nanoparticle loading; the drug nanoparticles contain acrylate groups that can be cross-linked with the acrylated biodegradable polymer in the porous hydrogel, thereby increasing the cross-linking density of the drug-releasing hydrogel, thereby enhancing the pore structure of the hydrogel, and promoting the stable loading of the drug nanoparticles in the hydrogel, thereby achieving a long-lasting release of the active drug ingredient; the above cross-linking can also limit the swelling performance of the hydrogel, and the low swelling rate can effectively absorb wound exudate and maintain the proper mechanical properties of the dressing.
[0011] In some embodiments of the present invention, in the drug-releasing hydrogel, the mass ratio of drug nanoparticles to porous hydrogel is (1-30):(70-99), such as (5-28):(72-95), (10-25):(75-90), (12-25):(75-88), (15-25):(75-85), (18-23):(72-87).
[0012] In some embodiments of the present invention, in the drug nanoparticles, the mass ratio of the phospholipid-acrylate polymer to the active drug ingredient is 1:0.1-10, such as 1:0.3-8, 1:0.5-7, 1:0.8-5, 1:1-4, etc.
[0013] In some embodiments of the present invention, in the porous hydrogel, the mass of the porogen accounts for 20-90% of the total weight of the porous hydrogel, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc. In the present invention, the porosity in the porous hydrogel can be regulated by adjusting the mass proportion of the porogen, thereby regulating the drug loading and mechanical strength, thereby regulating the drug release behavior of the drug-releasing hydrogel according to actual needs.
[0014] In some embodiments of the present invention, the phospholipid-acrylate polymer includes a polymer formed by phospholipids, polyethylene glycol and acrylic acid, wherein acrylic acid reacts chemically with the hydroxyl group at the end of the polyethylene glycol chain to form an ester bond, and this structure enables the phospholipid-acrylate polymer to have both the water solubility of the PEG chain and the reactivity of acrylic acid. It can not only stably exist in aqueous solution, but also effectively combine with hydrophobic components in the body, showing a good balance between hydrophilicity and hydrophobicity.
[0015] In some embodiments of the present invention, the phospholipid includes at least one of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE), dipalmitoyl-phosphatidylethanolamine (DPPE), distearoylphosphocholine (DSPC), dimyristoyl-phosphatidylethanolamine (DMPE), 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), and poly(lactide-co-glycolide) (PLGA).
[0016] In some embodiments of the present invention, the molecular weight of the polyethylene glycol is 1000Da to 25000Da, preferably 1000Da to 5000Da.
[0017] In some embodiments of the present invention, the acrylated biodegradable polymer comprises at least one of PEG acrylate (PEGA), PEG methacrylate (PEGMA), PEG diacrylate (PEGDA), disulfide-containing PEGDA (PEGSSDA), PEG dimethacrylate (PEGDMA), poly(2-hydroxyethyl methacrylate) (pHEMA), poly(acrylic acid) (PAA), polyacrylate, poly(methacrylic acid) (PMA), and polymethacrylate.
[0018] In some embodiments of the present invention, the number average molecular weight of the polyethylene glycol diacrylate is 500-8000, for example, it can be 500, 525, 550, 575, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 6000, 7000, 8000, etc.
[0019] In some embodiments of the present invention, the porogen includes at least one of polyethylene glycol (PEG), chitosan, agarose, dextran, hyaluronic acid, poly (methyl methacrylate) (PMMA), cellulose and its derivatives, gelatin and its derivatives, acrylamide and its derivatives.
[0020] In some embodiments of the present invention, the cellulose and its derivatives include at least one of methyl cellulose, ethyl cellulose, ethyl methyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, and hydroxyethyl cellulose.
[0021] In some embodiments of the invention, the active pharmaceutical ingredient comprises an anti-inflammatory drug, including nonsteroidal anti-inflammatory drugs (NSAIDs), such as diclofenac, etodolac, fenoprofen, flurbiprofen, ibuprofen, indomethacin, ketorolac, meclofenac, mefenamic acid, nabumetone, naproxen, oxaprozin, piroxicam, sulindac, tolmetin, celecoxib, meloxicam, rofecoxib, valdecoxib, aspirin, and steroidal anti-inflammatory drugs, including cortisone, prednisone, and dexamethasone.
[0022] In some embodiments of the present invention, the active pharmaceutical ingredient comprises an analgesic, including but not limited to acetaminophen, phenylamino uridine, acetylsalicylic acid, buprenorphine, butorphanol, fentanyl, fentanyl citrate, codeine, rofecoxib, hydrocodone, hydromorphone, hydromorphone hydrochloride, levorphanol, alfentanil hydrochloride, pethidine, pethidine hydrochloride, methadone, morphine, nalbuphine, opium, levomethadine, sodium hyaluronate, sufentanil citrate, capsaicin, tramadol, leflunomide, oxycodone, oxymorphone, celecoxib, pentazocine, propoxyphene, benzocaine, lidocaine, dezocine, clonidine, butalbital, phenobarbital, tetracaine.
[0023] In some embodiments of the invention, the active pharmaceutical ingredient comprises a local anesthetic, including amylocaine, ambucaine, articaine, benzocaine, benzonatate, bupivacaine, tetracaine, tetracaine, chloroprocaine, cinchocaine, cyclomethicaine, dibucaine, dimethoquine, dimethicaine, eucaine, etidocaine, hexacicaine, formocaine, fotocaine, hydroxyprocaine, isoprocaine, Bucaine, levobupivacaine, iodocaine, mepivacaine, meprocaine, mebuticaine, nicotinic acid, oxorcaine, oxadivacaine, oxybuprocaine, acetamipridoxine, phenacaine, piperocaine, pidocaine, pramoxine, aine, primacaine, procaine, procainamide, proparacaine, procicaine, pyrocaine, quinicaine, ropivacaine, trimevacaine, tetracaine, tolicaine, and topacine.
[0024] In some embodiments of the present invention, the active pharmaceutical ingredient includes at least one of an anti-inflammatory drug, an analgesic or a local anesthetic. To promote wound healing, multiple active pharmaceutical ingredients can be used simultaneously, such as an anti-inflammatory drug, an analgesic and a local anesthetic. For example, aspirin, lidocaine and ropivacaine are used simultaneously.
[0025] In some embodiments of the present invention, the active pharmaceutical ingredient may also include cytokines, growth factors, any wound healing agonists (or effective wound healing agents), including but not limited to small molecule agonists, peptide agonists, chemical agonists or mixtures thereof. In some embodiments of the present invention, growth factors may be, for example, platelet-derived growth factor, vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, TGF-β and mixtures thereof.
[0026] In some embodiments of the present invention, the drug nanoparticles are spherical or quasi-spherical, and have a size of 80 to 200 nm, such as 100 to 180 nm.
[0027] In some embodiments of the present invention, the zeta potential value of the drug nanoparticles is -35mV to -20mV, such as -30mV to -22mV.
[0028] In some embodiments of the present invention, the drug-releasing hydrogel can be in any shape, such as block, film, micro-hydrogel, etc. Micro-hydrogel is a cross-linked network particle with a size between submicron and micron, with a large specific surface area, strong mechanical properties of oscillation in fluid, slow drug release rate, and long drug release time.
[0029] In some embodiments of the present invention, the diameter of the pores in the porous hydrogel is 1-100 μm, such as 50-100 μm, 1-35 μm, 5-30 μm, 10-30 μm, 1-10 μm, etc.
[0030] The second aspect of the present invention provides a method for preparing the drug-releasing hydrogel, comprising the following steps:
[0031] A porogen, a drug nanoparticle solution and an initiator are added to the acrylic biodegradable polymer solution, and light curing is performed to obtain the drug-releasing hydrogel.
[0032] In some embodiments of the present invention, the drug nanoparticle solution is prepared by mixing an organic solution of a phospholipid-acrylate polymer with an organic solution of an active drug ingredient, dispersing the mixture of the two solutions in water, and then sonicating to obtain a drug nanoparticle solution.
[0033] In some embodiments of the present invention, the volume ratio of the organic solvent to water is 1:5-100.
[0034] In some embodiments of the present invention, the mass concentration of the phospholipid-acrylate polymer in the organic solution of the phospholipid-acrylate polymer is 0.01wt% to 1.0wt%, such as 0.03wt% to 0.8wt%, 0.05wt% to 0.6wt%, 0.1wt% to 0.5wt%, etc.
[0035] In some embodiments of the present invention, the mass concentration of the active drug in the organic solution of the active drug ingredient is 0.01wt% to 1.0wt%, such as 0.03wt% to 0.8wt%, 0.05wt% to 0.6wt%, 0.1wt% to 0.5wt%, etc.
[0036] In some embodiments of the present invention, the organic solvent of the drug nanoparticle solution is removed, the aggregates are removed by filtration, and the excess phospholipid-acrylate polymer is removed by dialysis to obtain a uniformly dispersed drug nanoparticle solution.
[0037] In some embodiments of the present invention, the mass concentration of the acrylated biodegradable polymer in the acrylated biodegradable polymer solution is 1 wt% to 50 wt%, such as 5 wt% to 45 wt%, 10 wt% to 40 wt%, 15 wt% to 30 wt%, 20 wt% to 25 wt%, etc.
[0038] In some embodiments of the present invention, the mass concentration of the drug nanoparticles in the drug nanoparticle solution is 0.01wt% to 1.0wt%, such as 0.03wt% to 0.8wt%, 0.05wt% to 0.6wt%, 0.1wt% to 0.5wt%, etc.
[0039] In some embodiments of the present invention, the organic solvent includes at least one of dimethyl sulfoxide, acetone, tetrahydrofuran, ethanol, methanol, and N,N-dimethylformamide.
[0040] In some embodiments of the present invention, the initiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone (Darocur1173), (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO), 1-hydroxycyclohexyl phenyl ketone (184), 2,2-dimethoxy-phenylacetophenone (BDK), benzophenone (BP), 2-isopropylthiothianthionone (2, 4 isomer mixture) (ITX), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (907), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl) butanone (369), phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide (819), benzoyl formate mixture (754), 1,1'-(methylenebis(4,1-phenylene))bis(2-hydroxy-2-methylpropan-1-one) (Irgacure 127).
[0041] In some embodiments of the present invention, the mass ratio of the acrylated biodegradable polymer to the initiator is 5 to 50:1, such as 10 to 40:1, 20 to 30:1, and the like.
[0042] In some embodiments of the present invention, the frequency of the ultrasound is 20KHz to 60KHz (such as 30KHz, 40KHz, 50KHz); the ultrasonic power is 80 to 130W (such as 90W, 100W, 110W, 120W), and the time is 1min to 10min, such as 3min, 5min, 8min, etc.
[0043] In some embodiments of the present invention, the photocuring is performed by cross-linking under ultraviolet light.
[0044] In some embodiments of the present invention, the intensity of the ultraviolet light is 80 to 150 mJ / cm 2 (e.g. 90mJ / cm 2 、100mJ / cm 2 、110mJ / cm 2 、120mJ / cm 2 、130mJ / cm 2 、140mJ / cm 2 ), time is 30s~5min.
[0045] In some embodiments of the present invention, the wavelength of the light is 250-380 nm, such as 280-350 nm, 300-330 nm, etc.
[0046] The third aspect of the present invention provides a use of the drug-releasing hydrogel in the preparation of a wound healing drug.
[0047] In some embodiments of the present invention, the wound comprises at least one of a burn, a trauma, a wound left by a surgical intervention (such as a dental operation, other surgical operations, etc.), a chronic wound, such as an ulcerative wound, a diabetic wound, such as a diabetic ulcer wound.
[0048] A fourth aspect of the present invention provides a device for wounds, comprising the drug-releasing hydrogel and, optionally, a base material.
[0049] In some embodiments of the present invention, the drug-releasing hydrogel can be provided in a desired size and shape by cutting the substrate material into a desired size and shape and peeling the drug-releasing hydrogel sheet from the substrate. The drug-releasing hydrogel can then be applied to a biological surface (e.g., a wound) or a medical surface (e.g., a surface of a medical device (e.g., a wound cover)). In some embodiments, the drug-releasing hydrogel is used to modify a wound dressing or a biological wound dressing that is compatible with functionalization by adding a matrix material. Examples of commercially available wound dressings that can be modified by adding a drug-releasing hydrogel include, but are not limited to, Biobrane TM , gauze, tape, bandages, etc. and other commercially available wound dressings, including but not limited to DUODERM TM TAGADERM TM and In some embodiments, the present invention provides a method for transferring a drug-releasing hydrogel to a desired surface (e.g., a soft surface). Such soft surfaces include, but are not limited to, skin, wound beds, tissues, artificial tissues, including artificial skin tissues such as organ-cultured skin tissues, Artificial tissue matrix, gel containing biomolecules, wound dressing and biological wound dressing. In some embodiments, the desired surface is contacted with a drug-releasing hydrogel, such as a drug-releasing hydrogel supported on a carrier, and pressure is applied to achieve transfer of the drug-releasing hydrogel from the carrier to the desired surface. In some embodiments, the pressure is about 10 to about 500 kPa. In some embodiments, the transfer is carried out in the absence of a solution substantially or completely. This dry transfer process does not involve exposing the biological components of the desired surface to an aqueous solution containing substances that may affect the activity of the biological components. In some embodiments, the transfer is carried out through the gas phase. In some embodiments, the transfer is carried out in an environment where the humidity is less than 100% saturation. In some embodiments, the transfer is carried out in the absence of liquid water.
[0050] In some embodiments, the drug-releasing hydrogel is used to modify an adhesive bandage comprising an adhesive portion (e.g., an adhesive strip) and an absorbent material, preferably treated or coated with a material (i.e., a non-adhesive material) to prevent adhesion to the adhesive portion. The wound or the absorbent pad includes a layer of non-adhesive material, such as Teflon, on the surface that will contact the wound. In some embodiments, the support material is an absorbent pad (e.g., a gauze pad or polymer foam), preferably treated or coated with a material (i.e., a non-adherent material) to prevent adhesion to the wound or comprising a non-adherent layer. The adherent material on the surface of the absorbent pad that contacts the wound, e.g. Or other suitable materials. In some embodiments, the non-adhesive material or layer is breathable. In some embodiments, the wound dressing comprises a gel former, such as a hydrocolloid, such as sodium carboxymethylcellulose. In some embodiments, the absorbent pad or gel former is fixed to a waterproof and / or breathable material. Examples include, but are not limited to, a semi-permeable polyurethane film. The waterproof and / or breathable material may also include an adhesive material for fixing the bandage to the subject's skin. The waterproof and / or breathable material preferably forms the outer surface of the adhesive bandage or pad, that is, the surface opposite to the surface containing the matrix that contacts the wound.
[0051] Examples of such adhesive bandages and absorbent pads include, but are not limited to, Range of wound dressings adhesive bandages and pads, from Range of wound dressings in adhesive bandages and pads, adhesive bandages and non-adhesive bandages. Kendall Curity Adhesive pads for series of wound dressings, Adhesive bandages and pads for a range of wound dressings, Adhesive bandages and pads for a range of wound dressings, Range of wound dressings, adhesive bandages and pads, Range of wound dressings, adhesive bandages and pads, TEGADERM TM Range of wound dressings, adhesive bandages and pads, Range of wound dressings, adhesive bandages and pads, Allevyn TM Series of wound dressings adhesive bandages and pads, A range of adhesive bandages and pads for wound dressings, and A range of adhesive bandages and pads for wound dressings.
[0052] In some embodiments, the devices of the present invention are used to modify medical devices, such as surgical meshes. Examples of commercially available surgical meshes that can be modified by adding a matrix as described below include, but are not limited to, polypropylene, polyester, polytetrafluoroethylene meshes, or absorbable biological meshes or biological meshes (biomeshes), including, but not limited to, ULTRAPRO TM Mesh, PROCEED TM Mesh, PROLENE TM Polypropylene mesh, Ethicon Physiomesh TM MERSILENE TM Polyester mesh, PARIETEX TM Mesh, DOLPHIN TM Polypropylene mesh, GORE INFINIT TM Mesh, PERFIX TM 、KUGEL TM 、3DMAX TM , BARD TM 、VISILEX TM 、XENMATRIX TM ALLOMAX TM 、SURGISISBIODESIGN TM and TIGR MATRIX TM .
[0053] The beneficial effects of the present invention are:
[0054] The drug-releasing nanoparticle-enhanced hydrogel of the present invention has a well-defined pore structure and is intended to achieve sustainable drug release and effective wound healing, especially for diabetic patients. The hydrogel may contain surface-modified anti-inflammatory and local anesthetic drug nanoparticles, which are cross-linked with the gel precursor to enhance structural integrity and provide sustained drug release. The drug delivery system can achieve more than 90% drug release, which can be adjusted within 4 to 72 hours, significantly improving wound healing rates and skin regeneration. The hydrogel is biocompatible, promotes re-epithelialization, angiogenesis and collagen regeneration, and leads to minimal scar formation. The invention solves the technical problem of providing a moist environment for wound healing while ensuring controlled drug release and structural stability, making it very effective for chronic wound management.
[0055] The nanoparticle-enhanced hydrogels described in this invention have several advantages over existing hydrogel platforms:
[0056] 1. Efficient drug nanoparticle preparation and simple drug compatibility.
[0057] 2. The structural integrity is enhanced due to the cross-linking of surface-modified drug nanoparticles with the hydrogel matrix.
[0058] 3. Controlled and sustained drug release, adjustable from 4 to 72 hours.
[0059] 4. Improve wound healing rate and skin regeneration rate, the healing rate is 17 times that of untreated wounds.
[0060] 5. Effective anti-inflammatory and analgesic properties, promoting re-epithelialization, angiogenesis and collagen regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 : Schematic diagram of the anti-inflammatory mechanism of the sustainable treatment platform of the technical solution of the present invention.
[0062] Figure 2 : Scheme of DNP and nanodrug-hydrogel composite preparation.
[0063] Figure 3 : SEM and DLS measurements of drug nanoparticles; ac) Typical SEM images and DLS size distribution of F-127 encapsulated DNPs (aspirin, lidocaine and ropivacaine, from left to right); df) Typical SEM images and DLS size distribution of DSPE-PEG-AC encapsulated DNPs-AC (aspirin, lidocaine and ropivacaine, from left to right).
[0064] Figure 4 : Zeta potential of DNPs without and with acrylate in water.
[0065] Figure 5:Morphology and drug release characteristics of drug-loaded hydrogels; a) Typical SEM image of drug nanoparticle gel (Gel-DNPs) loaded with surface unmodified acrylate; b) Cumulative release curves of bulk Gel-DNPs with different pore-forming factor components (40%-80%); c) Typical SEM image of drug nanoparticle gel loaded with surface modified acrylate (Gel-DNPs-AC); d) Long-acting cumulative release curves of bulk Gel-DNPs and bulk Gel-DNPs-AC with pore-forming factor fractions of 70%.
[0066] Figure 6 :a) Rheological curves showing that Gel-DNPs and Gel-DNPs-AC formed hydrogels under UV light induction; b) swelling and degradation properties of the two hydrogels.
[0067] Figure 7 :a) Schematic diagram of hydrogels of different shapes: block, film and micro hydrogel Gel-DNPs-AC, with a pore-forming factor fraction of 70%; b) Cumulative release curves of block, film and micro hydrogel Gel-DNPs-AC.
[0068] Figure 8 : Biocompatibility determination of Gel-DNPs-AC; a) Schematic diagram of biocompatibility testing of hydrogels with mammalian cells by Transwell; b) Viability of B-SC-1 cells treated with Gel-DNPs-AC for 24 and 48 hours, data reported as SD±mean (n=5); c) Fluorescence imaging of live / dead BSC-1 cells stained with a kit treated with Gel-DNPs-AC for 48 hours, where calcein AM (green) stained live cells and PI (red) stained dead cells, scale bar: 200 μm.
[0069] Fig. 9 : Wound healing study in diabetic mice; a) Schematic diagram of the animal experimental design to test the therapeutic effects of composite hydrogels in normal and diabetic mouse models; b) Representative images of wounds treated with or without composite hydrogels for 14 days; c) Schematic diagram of wound size at different time points, normalized to day 0; d) Qualification of wound size changes within 14 days after injury; *P<0.05, **P<0.01, ***P<0.001.
[0070] Fig.10: Assessment of re-epithelialization and angiogenesis; a) Immunofluorescence staining of cytokeratin 14 (CK14, red) in wounds on days 7 and 14, scale bar, 200 μm; b) Immunofluorescence staining of blood vessels (CD31, yellow) in wounded areas on days 7 and 14, scale bar, 50 μm; In all immunofluorescence staining images, cell nuclei were stained with DAPI; c) Quantification of vascular density; *P<0.05, **P<0.01, ***P<0.001.
[0071] Fig.11 : Evaluation of collagen regeneration and scarless healing; Drug-loaded hydrogel promotes scarless wound healing of diabetic wounds, a) H&E staining images of wounds after 7 and 14 days, scale bar, 200 μm (black arrow, epidermis; red arrow, skin appendages); b) Sirius red staining of wounded skin on day 14, scale bar, 100 μm; c) Quantification of total collagen deposition on day 14, *P<0.05, **P<0.01, ***P<0.001. DETAILED DESCRIPTION
[0072] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0073] Figure 1 The anti-inflammatory mechanism of the sustainable therapeutic platform is illustrated. The topical hydrogel releases a cocktail combination of anti-inflammatory drugs and local anesthetics on the wounds of diabetic mice. During the cross-linking process, the structure and sustained release of the hydrogel are enhanced by the surface properties of the drug nanoparticles. Inside the cell, the combination of drug molecules modulates signaling pathways and inhibits the secretion of PGE2, thereby achieving anti-inflammatory efficacy.
[0074] Example 1
[0075] This example prepares a drug nanoparticle, a mixture formulation combining anti-inflammatory and local anesthetic nanoparticles, such as Figure 2 As shown, active drugs (aspirin, ropivacaine and lidocaine) were encapsulated by Pluronic F-127 and DSPE-PEG-AC amphiphilic polymers, respectively, and drug nanoparticles were prepared by reprecipitation method. The specific process is as follows:
[0076] The organic drug molecules were dissolved in methanol, a good solvent, at a concentration of 1000 ppm; the polymer encapsulating agent was also dissolved in the same good solvent at the same concentration. The mixture of 200 μL of the drug solution (1000 ppm) and 200 μL of the polymer solution (1000 ppm) prepared above was rapidly injected and dispersed into 10 mL of ultrapure water, and a self-assembled drug nanoparticle mixture was prepared under the disturbance of ultrasonic high energy (100 W, 100 s). The organic solvent was removed by nitrogen purging, a small amount of aggregates were removed by filtration with a 0.22 μm filter membrane, and the excess polymer encapsulating agent was removed by dialysis to obtain drug nanoparticles uniformly dispersed in the aqueous solution.
[0077] The drug nanoparticle solution was dropped onto the surface of a silicon wafer, dried, and attached to a copper platform, and then coated with carbon to increase the conductivity of the organic particles. After the PEGDA hydrogel sample was freeze-dried, it was torn open with tweezers to observe its side cross-sectional morphology. The hydrogel sample was fixed on a copper platform and coated with gold to increase conductivity for observation.
[0078] In this embodiment, Pluronic F-127 (abbreviated as F-127) is a nonionic surfactant polyol that can promote the dissolution of hydrophobic drugs in physiological media to assemble DNP. Amphiphilic polymer (DSPE-PEG-AC) is also a typical encapsulant, but its polymer molecules contain acrylate groups (green dots), which can assemble DNPs-acrylic acid (DNPs-AC) and can cross-link with the gel precursor PEGDA. Then PEGDA can cross-link with DNPs-AC to enhance the pore structure of the hydrogel, thereby achieving sustained drug release.
[0079] Aspirin, ropivacaine, and lidocaine were encapsulated in nanoparticles by Pluronic F-127 or DSPE-PEG-AC to achieve water solubility and stability. Pluronic F-127 encapsulated aspirin, lidocaine, and ropivacaine DNPs were characterized by SEM and DLS (dynamic light scattering) measurements ( Figure 3 a, 3b and 3c), indicating that their particle sizes are 122 nm, 105 nm and 79 nm, respectively. These nanoparticles exhibit irregular shapes and low zeta potential values ( Figure 4 a). In contrast, aspirin, lidocaine, and ropivacaine DNPs-AC encapsulated with DSPE-PEG-AC polymer showed regular spheroidal shapes with particle sizes of 175 nm, 164 nm, and 101 nm, respectively ( Figure 3 d, 3e, and 3f). DSPE-PEG-AC provides uniform assembly of DNPs-AC and an outer layer distribution of acrylates, resulting in a zeta potential approximately three times higher than that of DNPs without acrylates ( Figure 4b). Larger zeta potential values lead to more stable distribution of drug nanoparticles in water. Meanwhile, surface acrylates can be cross-linked with PEGDA, promoting stable loading of DNPs-AC in hydrogel.
[0080] Example 2
[0081] This example prepares a drug-releasing hydrogel, which is prepared by cross-linking PEGDA, porous PEG and the DNPs solution prepared in Example 1. PEGDA and PEG are used to form hydrogels, which have been shown to have good biocompatibility, biodegradability and immunological inertness. PEG has been used as a porogen to introduce porosity into the hydrogel to improve the accessibility of drug loading. The specific process is:
[0082] PEGDA hydrogel was prepared by in situ free radical polymerization. The prepolymer solution contained 33wt% PEGDA hydrogel, PEG of different contents, accounting for 40%, 60%, 70%, 75%, 80% and the corresponding remaining PEGDA of the total weight of PEGDA hydrogel, 59wt% drug nanoparticle solution, and 8wt% initiator. The prepolymer mixture was added to the mold and heated under ultraviolet light (365nm, 120mJ / cm 2 ) for 1 minute. The acrylate on the surface of the drug nanoparticles encapsulated with DSPE-PEG-AC can be cross-linked with PEGDA to synthesize a more stable hydrogel framework loaded with drug nanoparticles.
[0083] Figure 5 a shows the morphology of the hydrogel loaded with DNPs (Gel-DNPs), which was prepared by using a precursor formulation of 10 wt% PEGDA, 70 wt% PEG, and 17.6 wt% DNPs solution. The PEG porogen provides a hydrogel structure with cave-like channels, which facilitates the loading of the DNPs solution. Therefore, the drug release properties of the hydrogel can be adjusted by adjusting the amount of the porogen to meet the needs of different application scenarios.
[0084] The effect of porous PEG components on drug release characteristics was studied by placing Gel-DNPs in a PBS solution shaken at 37°C. The specific process is as follows:
[0085] The DNPs-loaded hydrogel was placed in PBS in a flat-bottom centrifuge tube and shaken at 60 rpm in an incubator at 37°C to simulate the in vivo environment. 1 mL of drug release solution was regularly drawn from the centrifuge tube for UV-visible light testing. The same volume of fresh PBS was replaced at each interval to maintain perfect sedimentation conditions. The soaking solution was analyzed at the characteristic absorption peak wavelength of the drug by a UV-visible spectrophotometer. The cumulative release absorption of the drug-releasing hydrogel was calculated according to the following formula:
[0086] Cumulative Abs=V 0 A n +∑VA n-1
[0087] Among them A n and A n-1 are the drug absorption of the nth and n-1th samplings, respectively, V 0 is the initial volume of the drug release medium and V is the sampling volume.
[0088] Drug-releasing hydrogels were prepared by varying the porous PEG fraction from 20 wt% to 90 wt%. 致孔剂 =70%, the release time increases with the increase of porogen fraction ( Figure 5 b) At 70% PEG fraction, the complete release of the drug was achieved up to 12 h. However, the increase in porosity was accompanied by a decrease in structural strength. 致孔剂 = 70%, the full release time begins to decrease; for example, Φ 致孔剂 = 75% complete release time is 6 hours.
[0089] It is worth noting that excessive addition of the pore-forming factor ratio will lead to an increase in the surface area and structural instability of the hydrogel. This will cause the hydrogel to collapse rapidly in the body fluid, resulting in rapid drug release. In the in vivo environment simulation, Φ 致孔剂 = 80% of the Gel-DNPs disintegrated after 2 hours. This type of hydrogel is suitable for applications requiring rapid drug release and high local drug release concentration.
[0090] For chronic wound treatment, in order to maintain a steady-state concentration, the preparation of the gel precursor is controlled at Φ 致孔剂 =70%.
[0091] The surface acylation groups of drug nanoparticles are crucial for the formation of regular pore structures in the hydrogel. The hydrogel was cross-linked with DNPs-AC (Gel-DNPs-AC), and the precursor consisted of 10 wt% PEGDA, 70 wt% PEG, and 17.6 wt% DNPs-AC solution. Figure 5 As shown in (c), the Gel-DNPs-AC platform shows a well-defined pore structure compared with Gel-DNPs, indicating that DNPs-AC plays an important role in the formation of regular pores. The enlarged SEM image shows that the pore size in Gel-DNPs-AC varies in the range of tens of microns. Regular pores and channels facilitate the release of drugs from Gel-DNPs-AC hydrogels. By comparing the same PEG fraction (Φ 致孔剂=70%) of Gel-DNPs and Gel-DNPs-AC, and studied the effect of cross-linking between nanodrugs and hydrogels on drug release characteristics. Obviously, Gel-DNPs-AC showed sustained release performance. Gel-DNPs-AC showed a release time of more than 24 hours, and the cumulative drug release was higher than 90% ( Figure 5 d), indicating that the cross-linking between DNPs-AC and hydrogels resulted in long-term sustainable and complete release compared with the gel physically loaded with DNPs. The cross-linking between DNPs-AC and PEGDA may create a large number of stable attachment sites for nanodrugs on the hydrogel scaffold, enhancing the drug loading capacity of the composite hydrogel.
[0092] Swelling rate and dynamic rheology test of drug release hydrogel:
[0093] The swelling rate of the hydrogel in water was determined using the gravimetric method. The hydrogel sample was soaked in water until it reached a constant weight and then quickly removed from the water. The water on the surface of the hydrogel was removed with filter paper and weighed to obtain the equilibrium swelling mass. The equilibrium swelling rate (ESR) of the hydrogel was calculated using the following formula:
[0094]
[0095] Where W s is the weight of the hydrogel after swelling equilibrium; W d is the dry weight of the hydrogel (after freeze-drying).
[0096] The degradation rate was evaluated by weighing the samples that were freeze-dried after soaking. The hydrogel samples were soaked in water until constant weight, then taken out and freeze-dried. After removing the water, the samples were weighed to obtain the degraded mass. The degradation rate (DR) of the hydrogel was calculated as follows:
[0097]
[0098] Where W d is the dry weight of the hydrogel before immersion; W de is the dry weight of the hydrogel after immersion. The dynamic rheological properties of the hydrogel were tested by a rotational rheometer (HAAKE MARS III). The storage modulus and loss modulus were measured as a function of time and frequency under UV irradiation.
[0099] Analysis of dynamic rheological properties by time sweep testing ( Figure 6a). The storage modulus (G') is greater than the loss modulus (G") after phototreatment. Under UV irradiation, the two gel precursors with two DNPs changed from liquid to solid within seconds and immediately exhibited elastic behavior. The storage modulus of Gel-DNPs-AC was greater than that of Gel-DNPs, indicating that the participation of DNPs-AC in the hydrogel framework enhanced the mechanical properties of the hydrogel. The improved mechanical properties are consistent with the well-defined pore structure of the Gel-DNPs-AC sample. The swelling ratio and degradation rate of the two structured hydrogels were evaluated in PBS buffer (pH 7.4). Figure 6 As shown in b, both hydrogels degraded by 97% after being immersed in PBS for one week, indicating that the hydrogels have good biodegradability. The water absorption capacity of Gel-DNPs-AC is significantly lower than that of Gel-DNPs, indicating that Gel-DNPs-AC has a rigid framework with a porous structure. The acrylate surface modification on DNPs-AC increases the cross-linking density of the composite hydrogel and leads to the formation of a regular pore structure, which limits the swelling properties of the hydrogel. The swelling properties of the hydrogel highly indicate the absorption of wound exudate by wound dressings. The low swelling rate of the hydrogel is beneficial to maintain the mechanical strength for skin treatment applications.
[0100] This example also studies the effect of hydrogel shape on drug release. Figure 7 As shown in a, a 70% porogen and DNPs-AC precursor solution were added to the mold and cured under UV light to form bulk hydrogels, film hydrogels, and micro hydrogels. The microgel had the slowest release rate among the three shapes, which may be related to the larger specific surface area of the microgel and the different mechanical properties of oscillating in the fluid. The film hydrogel suitable for skin treatment showed release characteristics comparable to those of the bulk hydrogel, and the complete release time was shorter than 24 hours ( Figure 7 b).
[0101] Example 3
[0102] In this example, the biocompatibility of Gel-DNPs-AC was evaluated by MTT and cell staining assays. The specific process was as follows:
[0103] Mammalian BS-C-1 cells were cultured in modified Dulbecco's medium containing 10% fetal bovine serum and 1% penicillin / streptomycin at 37°C and 5% CO. 2 The cell viability and cytotoxicity of Gel-DNPs-AC in vitro were evaluated by MTT test and calcein AM test. 4 BS-C-1 cells were inoculated into a 24-well cell culture plate and allowed to adhere overnight. The drug-releasing hydrogel was then cut into cylindrical shapes (6 mm*2 mm) and placed in a Transwell chamber, which was then placed on top of the cells to allow the hydrogel to soak and release the drug. The cells were incubated at 37°C and 5% CO2 Incubate in the presence of 5% paraformaldehyde for 24 or 48 hours. After incubation, MTT was added to each well and incubated for another 4 hours. After adding dimethyl sulfoxide, the absorbance (OD570) of each well was measured using a microplate reader (BioTekCytation 3) and the background was subtracted. Cell activity was calculated according to the following formula:
[0104]
[0105] in is the average absorbance of the treatment group, A c is the average absorbance of the control group.
[0106] The cell compatibility of Gel-DNPs-AC was tested by a live / dead cell activity assay kit. Cells were seeded as described above and incubated with the hydrogels immersed in Transwell. Calcein AM solution and propidium iodide (PI) solution were then added and incubated for 30 minutes and 10 minutes, respectively. The samples were washed three times with PBS and observed by confocal microscopy.
[0107] Three gels DNPs-AC gels were studied using the above-described Transwell apparatus to evaluate the release of the drug or the leaching of monomer residues. Mammalian cells (BS-C-1) were treated with the hydrogels placed in the Transwell inserts ( Figure 8 a). All Gel-DNPs-ACs showed no significant cytotoxicity, as shown by approximately 100% cell viability after 48 h of incubation ( Figure 8 b). Fluorescence staining showed that cells treated with hydrogels containing three types of DNPs-AC were similar to those of the control group ( Figure 8 c), as evidenced by the bright fluorescence of live cells (Calcein AM) and the absence of fluorescence of transaction cells (PI). These observations further confirmed the good biocompatibility of Gel-DNPs-AC.
[0108] Example 4
[0109] This example evaluates the efficacy of Gel-DNPs-AC in wound healing in diabetic mice. The specific process is as follows:
[0110] Diabetic mice were induced by the streptozotocin (STZ) method. STZ was dissolved in citric acid and sodium citrate buffer, and each mouse was intraperitoneally injected with STZ (180 mg / kg) to induce diabetes. The blood glucose level was measured after the mice fasted overnight. The blood glucose level was stable and exceeded 20 mmol / L after 10 days of injection, indicating that the model was successfully established. For each normal and diabetic mouse, a circular wound with a diameter of 1 cm was created on the hairless back skin for subsequent treatment. The diabetic mice were randomly divided into three groups (n=5). On days 0, 2, 4, 6, 8, and 10 after wound establishment, blank hydrogel and Gel-DNPs-AC were used for treatment, respectively. The mice were killed on days 7 and 14, and the skin tissues at the back wound site were collected. The tissues were fixed with 4% paraformaldehyde, embedded in paraffin, and stained with hematoxylin-eosin (H&E), picrosirius, and immunofluorescence staining of CK14 and CD31.
[0111] Compared with the control group, the hydrogel significantly accelerated wound closure ( Fig. 9 ). The healing of diabetic wounds was explored by applying Gel-DNPs-AC gel patches on excisional wounds in diabetic mice ( Fig. 9 a). Anti-inflammatory drug DNPs-AC and local anesthetic DNPs-AC were incorporated into the composite hydrogel by cross-linking for cocktail therapy. Each gel patch contained a mixture of 40 μg aspirin, 30 μg ropivacaine and 30 μg lidocaine. Fig. 9 As shown in b, wounds of diabetic (Db) mice treated with Gel-DNPs-AC showed a higher closure rate than those of untreated mice and the pure gel group. By day 14, wounds of diabetic mice treated with Gel-DNPs-AC were completely closed compared with those of the control group ( Fig. 9 d). The wounds in the Gel-DNPs-AC treated group recovered well, healing to 1.16% of the original wound size, showing similar or better wound closure rates in the same rodent model (STZ-induced diabetic mice) compared to previous studies using anti-inflammatory drugs to treat chronic wounds. In the first four days, the wound area in the Gel-DNPs-AC group closed faster than that in the normal mouse group ( Fig. 9 c) These results suggest that the porous hydrogels promoted wound closure in the initial stage, and Gel-DNPs-AC helped diabetic wounds recover as effectively as normal wounds.
[0112] Evaluation of re-epithelialization and angiogenesis: Histological analysis showed enhanced re-epithelialization and angiogenesis in wounds treated with gel DNPs-AC ( Fig.10The re-epithelialization rate of the diabetic wound site was evaluated by staining tissue sections collected on days 7 and 14 with cytokeratin 14 (CK14, a marker of basal keratinocytes). On day 7, the midpoint of the healing period, half of the wound gap was filled with a basal keratinocyte layer (CK14) in the Gel-DNPs-AC group. + ). In contrast, the migration of keratinocytes in other control groups was significantly slower than that in the treatment group ( Fig.10 a). On day 14, the migration of basal keratinocytes was completely completed in both the Gel-DNPs-AC group and the normal mouse group. In the Gel-DNPs-AC group, a more clearly stratified epithelium was observed compared with that in normal mice without gel. In contrast, in the no treatment group and in diabetic mice treated with gel alone without drug loading, the keratinocyte layer was not closed, while migration, proliferation, and differentiation were still ongoing. These observations demonstrate that the sustained anti-inflammatory and pain-relieving effects of Gel-DNPs-AC effectively accelerate the migration of keratinocytes, thereby promoting the re-epithelialization of diabetic wounds. To evaluate angiogenesis in diabetic wounds, platelet endothelial cell adhesion molecule-1 (CD31 + ) markers to quantify the capillary density in the mid-stage (day 7) and final stage (day 14) of wound healing. In both stages, the capillary density (CD31 + ) was significantly higher than other control groups ( Fig.10 b and 10c, P < 0.001). The results showed that the composite Gel-DNPs-AC promoted rapid angiogenesis and helped chronic wounds transition from the prolonged inflammatory phase to the proliferative phase.
[0113] Collagen regeneration and scar-free healing assessment: Collagen deposition and scar formation were assessed using histological staining. Gel-DNPs-AC promoted collagen regeneration and resulted in minimal scarring ( Fig.11 To evaluate scar-free skin repair at diabetic wound sites, epidermal thickness was characterized by hematoxylin-eosin (H&E) staining. H&E staining demonstrated inflammatory cell status, fibroblast proliferation, and wound neovascularization ( Fig.11a). On day 7, both the normal mouse group and the untreated diabetic mice showed a large number of inflammatory cell infiltrations. In contrast, the pure gel group and the Gel-DNPs-AC group showed fewer inflammatory cells, and some skin appendages (triangular arrows) regenerated, indicating that the PEGDA hydrogel contributed to the rapid functional recovery of skin tissue. On day 14, a large number of skin appendages and hair follicles were formed in the hydrogel-treated group, while far fewer skin appendages and hair follicles were observed in the other control groups. Among the four groups, the Gel-DNPs-AC group showed the most effective regeneration, with regular arrangement of collagen fibers and skin appendages and the thinnest new epidermis compared with all other control groups (black arrows). This suggests that the nanodrug-hydrogel composite sustainable treatment platform can regulate the infiltration of inflammatory cells in diabetic wounds, promote the regeneration of skin tissue and the proliferation of fibroblasts, and make the skin scar-free. Collagen regeneration, a key indicator of wound healing, was evaluated in the Gel-DNPs-AC treatment. Sirius red dye dyes collagen red and other tissues yellow. The density and depth of the two colors were compared to determine the collagen content at the wound site. As Fig.11 As shown, the Gel-DNPs-AC group regenerated a large amount of collagen with high-density red areas at the wound site. On day 14, the three control groups had less red collagen (accounting for 81% of the total healing area, P < 0.01) compared with the collagen content of the Gel-DNPs-AC group (accounting for 81% of the total healing area, P < 0.01) ( Fig.11 b and 11c). Collagen regeneration is neat and flat, revealing that the enhanced wound treatment method of the present invention facilitates scarless wound healing.
[0114] Dental treatment fillings: As mentioned above, the shape of the drug-loaded hydrogel platform is ductile, and the release effect of its different shapes has been studied. Therefore, this hydrogel drug carrying platform can be used as a wound filler in dental treatment to release the active drug ingredients in the affected area in a sustained manner. It is characterized by good biocompatibility, biodegradability, no need for surgical removal, and is soft enough to be suitable for such treatment scenarios.
[0115] Used as a postoperative filler: As mentioned above, the shape of the drug-loaded hydrogel platform is ductile, and the release effect of its different shapes has been studied. Therefore, this hydrogel drug-loaded platform can be used as a postoperative wound filler to release active drug ingredients in the affected area in a sustained manner. It has good biocompatibility and biodegradability. Compared with the traditional gauze filling method, it does not require surgical removal and is suitable for such treatment scenarios.
[0116] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A drug-releasing hydrogel, characterized in that: include: Drug nanoparticles, including active pharmaceutical ingredients encapsulated by phospholipid-acrylate polymers; A porous hydrogel comprising an acrylated biodegradable polymer and a porogen cross-linked to form a porous hydrogel; The porous hydrogel is loaded with the drug nanoparticles.
2. The drug-releasing hydrogel according to claim 1, characterized in that: The drug-releasing hydrogel satisfies at least one of the following conditions: (I) The mass ratio of the drug nanoparticles to the porous hydrogel is (1-30):(70-99); (II) In the porous hydrogel, the mass of the porogen accounts for 20 to 90% of the total weight of the porous hydrogel; (III) In the drug nanoparticles, the mass ratio of the phospholipid-acrylate polymer to the active drug ingredient is 1:0.1-10.
3. The drug-releasing hydrogel according to claim 1, characterized in that: The phospholipid-acrylate polymer includes a polymer formed by phospholipid, polyethylene glycol and acrylic acid.
4. The drug-releasing hydrogel according to claim 1, characterized in that: The acrylated biodegradable polymer includes at least one of PEG acrylate, PEG methacrylate, PEG diacrylate, disulfide-containing PEGDA, PEG dimethacrylate, poly(2-hydroxyethyl methacrylate), poly(acrylic acid), polyacrylate, poly(methacrylic acid), and polymethacrylate.
5. The drug-releasing hydrogel according to claim 1, characterized in that: The porogen includes at least one of polyethylene glycol, chitosan, agarose, dextran, hyaluronic acid, poly(methyl methacrylate), cellulose or its derivatives, gelatin or its derivatives, acrylamide or its derivatives.
6. The drug-releasing hydrogel according to claim 1, characterized in that: The active pharmaceutical ingredient includes at least one of an anti-inflammatory drug, an analgesic, or a local anesthetic.
7. A method for preparing the drug-releasing hydrogel according to any one of claims 1 to 6, characterized in that: The following steps are involved: A porogen, a drug nanoparticle solution and an initiator are added to the acrylic biodegradable polymer solution, and light curing is performed to obtain the drug-releasing hydrogel.
8. Use of the drug-releasing hydrogel according to any one of claims 1 to 6 in the preparation of a wound healing drug.
9. The use according to claim 8, characterized in that: The wound comprises at least one of a burn, a trauma, a wound left by a surgical intervention, and a chronic wound.
10. A device for wounds, comprising the drug-releasing hydrogel according to any one of claims 1 to 6, and optionally a base material.